The Common Threads of National Cultures. Issue 1 (February 2015) - Venaik, Sunil; Brewer, Paul
Culture related research in international marketing focusses largely on cultural relativism, that is, on cultural differences between countries. It examines the implications of national culture differences and how to manage the differences while doing business across national borders. These discussions are either framed within the emic versus etic debate, or under the rubric of national culture dimensions. Our paper addresses the equally important but largely ignored question of cultural universalism, that is, how nations are culturally similar. Using the GLOBE national culture dimensions data, we find significant similarities among the GLOBE nations. Our paper contributes to the cultural relativism versus universalism debate, and extends marketing theory with a "universal culture" approach that we believe can enhance understanding and cooperation among international business managers. Overall, our findings have important implications for scholars and practitioners.